The impact of workplace safety and customer misbehavior on supermarket workers' stress and psychological distress during the COVID-19 pandemic. Issue 3 (16th March 2022) - Mayer, Brian; Helm, Sabrina; Barnett, Melissa; Arora, Mona
Abstract : Purpose: Essential frontline workers in the retail sector face increased exposure risks to coronavirus disease 2019 (COVID-19) due to frequent interactions with the general public. Often these interactions are fraught with controversies over public safety protocols. The purpose of this study is to examine the impacts of frontline workers' perceptions of workplace safety and customer misbehaviors on their stress and psychological distress to inform managing workplace health and safety during public health crises. Design/methodology/approach: The authors conducted an online survey of 3, 344 supermarket workers in the state of Arizona (US) during the state's first COVID-19 pandemic wave in July 2020. Measures included mental health distress, and perceptions of workplace safety and customer behaviors. The authors utilized a mixed-methods approach combining multiple regression analyses with qualitative analyses of open-ended comments. Findings: Workers reported high rates of stress and psychological distress. Increases in mental health morbidity were correlated with perceptions of being unsafe in the workplace and concerns about negative customer encounters. Qualitative analyses reveal frustration with management's efforts to reduce risks intertwined with feelings of being unsafe and vulnerable to threatening customer encounters. Practical implications: The findings highlight the need to provide and enforce clear safety guidelines, including how to manage potential hostile customer interactions, to promote positive health workplace management during a pandemic. Originality/value: This study is among the first to assess the COVID-19 pandemic's impact on the mental health of non-health care frontline essential workers and presents novel insights regarding perceived customer misbehavior and need for management support and guidance in a public health crisis.